Efektivitas Penggunaan Aplikasi Whatsapp Dalam Metode Pembelajaran Daring - Salsabila Ladesta Susanto; Priatna Priatna; Isa Wijayanti (Lembaga Pengembangan Kinerja Dosen, 2023)
Lack of education in people's lives will of course hinder the progress and development of a country, and it will be difficult for the prosperity and well-being of its people to be realized. The aim of this research is to determine the effectiveness of online learning using the WhatsApp application for members of HIMAKOM 2019, BSD, South Tangerang City. Effectiveness means there is an influence that can produce results, efficiency and effectiveness. WhatsApp is one of the most commonly used communication applications on smartphones to interact, communicate and discuss and is even used for learning. Researchers use stimulus response theory in which the important learning is input in the form of stimulus and output in the form of response. Stimulus is whatever the teacher gives to students, while response is the student's reaction or response to the stimulus given by the teacher. The total population and sample are HIMAKOM members, totaling 58 BSD students, South Tangerang class of 2019. The results of hypothesis testing show that understanding the effectiveness of using the WhatsApp application has quite a significant effect on online learning, as evidenced by the t-count of 8.273 > 1.671 which is greater than t- table or significant value t < a = 0.05, then the effectiveness of using the WhatsApp application (X) influencing online learning (Y) is significant. This means that Ha is accepted and H0 is rejected, so it can be concluded that the effectiveness of using the WhatsApp application has a significant effect on online learning.